The confident forecaster. Lessons from the upscaling of the electricity industry in England and Wales. Issue 3 (3rd April 2017) - Luis Madureira, Nuno
Abstract: This article analyses the upscaling technological stage in the life cycle of capital-intensive technologies from the business history viewpoint. We correspondingly demonstrate how the pursuit of technological trajectories based on systematic increases in the size and power capacities of units pushed a new class of professionals, skills and procedures to the forefront of business decision-making. From 1958 onwards, forecasting framed and sharpened organisational insight into problems. Drawing on archival data on coal-fired, oil-fired and nuclear powered stations in England and Wales, the final section proceeds to measure the gap between reality and forecasts and singles out three major hypotheses to explain forecasting errors: inability to predict rapid changes outside the model (inter-fuel substitution); disregard of technical shortcomings in replication and standardisation, and overconfidence in extrapolating cost reductions at higher capacity levels.